Wave attenuation of saltmarsh vegetation under storm conditions - Caldera, Ganga; Stolle, Jacob; Bang, Damien Pham Van; Cornett, Andrew; Murphy, Enda; Nistor, Ioan (Coastal Engineering Proceedings, 2022)
Nature-based solutions (NbS) for coastal protection has recently gained increased attention worldwide as a sustainable, economical and eco-friendly alternative to conventional grey structures, particularly under the threat of climate change (Temmerman et al. 2013). Wave energy dissipation by vegetation can be parameterized by the total horizontal force acting on the plant; expressed using a Morison-type equation considering only the form drag component (Dalrymple et al. 1984). Modelling wave-vegetation interaction is challenging in a laboratory environment (Lara et al. 2016) and it is difficult to accomplish a realistic representation of a plant’s biomechanical behavior and geometry using plant mimics or surrogates. Few studies have modelled real saltmarsh vegetation in large scale laboratory facilities (Moller et al. 2014; Maza et al. 2015) and quantified wave attenuation, particularly for engineered living shorelines (Maryland DoE, 2013). Further research is needed, particularly in the Canadian context, to investigate the capacity of different saltmarsh species to effectively attenuate waves and wave runup under storm conditions, to examine the plant’s drag coefficient and to bridge the gap to develop technical design specifications for the detailed design of living shorelines.
Keywords: PhamVanBang_Damien

Deformation of Spartina patens and Spartina alterniflora stems under irregular wave action - Markov, Acacia; Stolle, Jacob; Henteleff, Ross; Nistor, Ioan; Pham Van Bang, Damien; Murphy, Enda; Cornett, Andrew (Coastal Engineering Journal, 2023)
Keywords: PhamVanBang_Damien